(untitled) (Archaeologia Adriatica, 2017)
This paper discusses a Late Antiquity lamp in the Archaeological Museum in Split which came to the author’s attention due to the illustration of a Biblical scene which dominates its central disc. In previous publications, the central iconography of this lamp has been interpreted as an Old Testament account of three Jewish youths refusing to bow down to the Babylonian King Nebuchadnezzar. On Old Christian lamps, this very interesting scene most frequently shows the moment when the youths stand in front of Nebuchadnezzar and the idol, and there are several variations of it. This paper suggests different possible interpretations of the iconography, as it is highly probable that there is room for new views and interpretations within its variations. The objective of this paper is not to list and catalogue all known artefacts, but rather to demonstrate, based on the available literature, that interpreting iconography is not always simple, and that there is room for new interpretations even in scenes which are believed to have been defined in terms of their iconography.